Penggunaan Kahoot sebagai Media Pembelajaran pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Islam Indragiri - Susanto, Bayu Fajar; Andriansyah, Andriansyah; Widyawati, Widyawati; Maulana, Raju; Muchlis, Muchlis; Dina, Syafrina; Guntur, SM. (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
This study aimed to test the effectiveness of using Kahoot as a learning media to improve students' learning outcomes in the Marketing Management course. The research was conducted on students of the Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Indragiri. The research method used was a Quasi Experimental Design with a pretest-posttest control group design. The research sample consisted of 100 students divided into two groups, namely the control group and the experimental group. The results of the study showed a significant difference in students' learning outcomes between the group that used Kahoot as a learning media and the group that used conventional learning methods. The t-test results showed a significant improvement in students' learning outcomes in the experimental group, with a mean posttest score of 84.07 compared to the control group, which only achieved a mean posttest score of 73.83. This indicates that the use of Kahoot as a learning media can improve students' learning outcomes in the Financial Management course. Based on the research results, it is concluded that Kahoot can be used as an effective learning media to improve students' learning outcomes in the Financial Management course. As a suggestion, the use of Kahoot as a learning media can be applied to other courses as an alternative to improve the quality of learning in higher education. Additionally, further research can be conducted involving a larger sample size and more complex research design to test the effectiveness of Kahoot in using learning media at a higher level.